2019
DOI: 10.1002/mds.27831
|View full text |Cite
|
Sign up to set email alerts
|

Pavement patterns can be designed to improve gait in Parkinson's disease patients

Abstract: Background Public spaces are usually designed with respect to various patient populations, but not Parkinson's disease. The objective of this study was to explore what type of easily applicable visual cueing might be used in public spaces and some interiors to improve gait in people with Parkinson's disease. Methods Thirty‐two patients with freezing of gait walked an 8‐meter track on 6 different floor patterns in single‐ and dual‐task conditions in random sequence. The reference pattern was a virtual large tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 54 publications
0
35
0
Order By: Relevance
“…Increasing background step length would make the SE less significant, thereby reducing the likelihood of freezing (11,14). Transverse lines on floor are well-known strategies to reduce FOG (25)(26)(27). In recent years, wearable laser lights have been designed to deal with FOG in PD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing background step length would make the SE less significant, thereby reducing the likelihood of freezing (11,14). Transverse lines on floor are well-known strategies to reduce FOG (25)(26)(27). In recent years, wearable laser lights have been designed to deal with FOG in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Strips on the floor may be more suitable for indoor FOG rehabilitation, while wearable laser lights offer the potential for alleviating freezing in daily activities. A recent research showed that pavement patterns designed in the form of large transversal visual cues could help improve gait in PD patients (27), and this may be a feasible strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Because pavement characteristics have been implicated several times in the risk of falling, fear of falling and gait disturbances, it should be one of the main intervention areas for people with PD. For instance, it was recently suggested that PD patients may benefit from floor patterns incorporating transverse oriented large rectangular visual cues [58], although no further details on floor adaptations were obtained. In addition, visual and auditory cueing techniques, e.g., transverse lines on the walkway, have been used as an effective component of locomotor therapy for people with PD [68][69][70][71] and are recommended at Hoehn-Yahr stage II [72].…”
Section: Discussionmentioning
confidence: 99%
“…To survey the circumstances surrounding falls, Stack et al [30,34] developed two cross-sectional design studies where questionnaires were used, and found trip hazards to be the main driver of sudden falls or near falling, namely uneven pavements, curbs, steps, skirting boards, doorways, and carpets. In addi- [57]; 2010 [46] Doorways/Lights Ashburn et al [32] Floor surface/Stair rails/Height of shelves Cole et al 2011 [33] Floor surface Floor surface Cowie et al 2010 [47]; 2011 [49] Doorways Ehgoetz et al 2013 [56] Doorways/Confined spaces/Open space/Lights Gál et al [58] Floor surface Galna, et al 2013 [13] Obstacle course Gazibara et al 2014 [35]; 2016 [36] Floor surface/Obstacle Giladi et al 1992 [41] Narrow spaces Gray et al 2000 [31] Floor [44] Narrow spaces Slaug et al 2013 [62] Housing accessibility Stack et al 1999 [30]; 2013 [34] Floor surface/Steps/Confined spaces/Doorways Stegemöller et al 2012 [51] Obstacle course tion, steps and doorways were reported to be the primary locations of such events within the home. Similarly, in a prospective-cohort study where fall diaries were used to assess fall related characteristics, Gray et al [31] found carpets to be the most common location of falls, referring further confined spaces to be also important fall locations.…”
Section: Fall-related Outcomesmentioning
confidence: 99%
See 1 more Smart Citation